What Is the Public Role of the University? A Proposal for a Public Research Agenda - Biesta, Gert; Kwiek, Marek; Lock, Grahame; Martins, Herminio; Masschelein, Jan; Papatsiba, Vassiliki; Simons, Maarten; Zgaga, Pavel (My University, 2009)
With a view to meeting the demands of the knowledge economy and taking up a leading role in its further development, Europe and its member states are urging universities and institutions for higher education more generally to innovate and modernise themselves. Organisational structures, governance and management systems, curricula and teaching methods, and funding and incentives mechanisms are no longer considered to be adequate to guarantee that European universities can keep up with global competition in education, research and innovation. Innovation and modernisation are also considered to be necessary with regard to the public (i.e. social, cultural and political) role of universities. Today’s knowledge-intensive economies and societies are regarded as in need of up-to-date policies on equal opportunities, participation and access, and of strategies for knowledge-driven local and regional economic, social and cultural development. In addition to this and based on a concern about European citizenship, democratic involvement and social cohesion, there is a requirement for the development of curricula, extra-curricular activities and participation structures that offer students opportunities to develop civic competencies.
Keywords: public university; public role; European universities; public agenda; the role of the university; public responsibility; modernisation agenda; European Commission; civic role; civic engagement